PENGARUH LOKASI, PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Konsumen Alfamart Brayo Timur CV. Surya Abadi) - Tri Nugroho, 12.05.51.0175; Yulianto, Heru (Students Journal of Economic and Management, 2016)
This study aims to determine the effect of location, price perception, and quality of service either partially or simultaneously on consumer purchasing decisions Alfamart Brayo Timur CV. Surya Abadi, Singorojo, Kendal. The population in this study is that consumers who were around in Alfamart Brayo East. Sampling was done by using purposive sampling method and number of samples to be processed into the research data of 100 questionnaires. Methods of data analysis used in this research is descriptive and quantitative analysis. The results of this study indicate that the location, price perception and quality of service positive and significant impact on purchasing decisions. Keywords: Locations, Perceptions of Price, Quality of Service and Purchase Decision.